DETERMINASI MAKROEKONOMI, AKSESIBILITAS DAN DEMOGRAFI TERHADAP ADOPSI CENTRAL BANK DIGITAL CURRENCY: STUDI KOMPARATIF INDONESIA, TIONGKOK, DAN BAHAMAS - Feryani, Dwin; Darmayanti, Novi; Nurhidayat, Esti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the simultaneous influence of macroeconomic, accessibility, and demographic factors on the adoption level of Central Bank Digital Currency (CBDC) through a comparative study in Indonesia, China, and the Bahamas. The method employed is a mix-method approach with a Sequential Explanatory design. Quantitative analysis was conducted on 34 provinces in Indonesia using panel data regression with a Random Effect Model via EViews 12, while qualitative analysis was carried out through a Systematic Literature Review with the assistance of NVivo 12. The results show that all three variables significantly influence CBDC adoption. Partially, macroeconomic conditions, digital infrastructure accessibility, and the level of bank account ownership each have a positive and significant effect. Simultaneously, these factors form a crucial foundation in supporting the successful implementation of CBDC. These findings indicate that technology readiness, financial literacy, and adaptive policy strategies are key to transforming the financial system through CBDC.